Challenges in E3 Listening Skills: Perspectives of Universitas Advent Indonesia Students - Nurjanah, Anisa; Panjaitan, Nelson Balisar (LPPM Institut Pendidikan Nusantara Global, 2024)
This study investigated Universitas Advent Indonesia's perceptions of the challenges and importance of E3 English listening skills in the context of academic and career development. Using a quantitative approach and data collection through a closed Likert-type questionnaire, 125 students from various study programs at Universitas Advent Indonesia responded to the study. The analysis showed that most students experienced several challenges in developing their listening skills, with 45.3% agreeing that such barriers existed. However, they also recognize the importance of listening skills, with 49.67% agreeing that it is vital to their academic success. Furthermore, 52.97% of the students agreed that the strategies used in the listening test were effective methods to improve their comprehension. In addition, most respondents supported recommendations to improve the teaching and learning of listening skills at Adventist University, with 50.93% agreeing with such efforts. This study sheds important light on the development of listening skills in higher education and provides valuable insights for efforts to improve them.